Performance of three-phase three-wire cascaded H-bridge multilevel inverter-based shunt active power filter - Musa Yusup Lada; Mohd Amran Mohd Radzi; Jasronita Jasni; Hashim Hizam; Auzani Jidin; Syahrul Hisham Mohamad (Institute of Advanced Engineering and Science, 2020)
Multilevel inverter (MLI) becomes more significant in Active Power Filter (APF) application due to capability to its produce low harmonic output current in which at the same time improving performance of APF. Among the topologies of MLI, Cascaded H-Bridge (CHB) is the most popular topology with less power devices requirement and simple design. MLI CHB is also capable to produce possible output voltage at twice of the number of DC source which in this case of APF is the best suited topology to replace with the conventional six -step inverter. This paper presents the performance of three- phase three-wire CHB MLI used in Shunt Active Power Filter (SAPF) based on Direct Current Control (DCC) and Indirect Current Control (ICC) schemes. Both schemes are developed and verified in MATLAB/Simulink. The simulation results show that both current control algorithms are capable to mitigate load current with Total Harmonic Distortion below than the permissible value based on IEEE 519 standard.